(untitled) (Bioagro, 2021)
The impact of water stress on antioxidant enzyme activities, proline, soluble sugars, and carotenoids contents found in Digitaria commutata and Cenchrus ciliaris plants was investigated. Two different watering regimes were used on plants over a period of three months. Water stress decreased total chlorophyll content in plants, but increased carotenoids content. Interestingly, no change was observed in the quantum yield of PSII photochemistry (Fv/Fm). Malondialdehyde (MDA) content increased to a higher extent in both species. Enhanced activities of all the enzymes (peroxidase, catalase, and superoxide dismutase) studied, except for catalase in the roots were observed. Proline and soluble sugars contents increased significantly following water stress exposure. No clear differences were found between both species. The results link drought tolerance of Digitaria commutata and Cenchrus ciliaris plants with better capabilities of anti-oxidative system. Additionally, it is linked to the accretion of osmoprotectants proline and soluble sugars when exposed to drought.